Online Learning during Pandemic Period: a Challenge, Hope, and Solution - Nise Samudra Sasanti (J-Litera: Jurnal Kajian Bahasa, Sastra dan Budaya Jepang, 2021)
Emerging of Corona Virus Disease (COVID-19) by the end of 2019 changes the learning system into online learning. All parties are not yet ready to change using different teaching methods and online applications. All institutes, either governmental or private institutes, are demanded to quickly carry out innovations to keep the learning going. On that score, the educators are demanded to start creating changes by prioritizing variety in teaching, by shifting to use internet network. One of the changes is by arranging more interesting and various teaching media to be easily accepted and learned by students at home without using an internet connection. It is done so that it will not add more burden to the students’ parents. This research aims to determine the challenges, hopes, and solutions of online learning during the pandemic period. The method used for this research is an analytic descriptive qualitative method using research instruments in the form of questionnaires shared by using WhatsApp group and emails. The total respondents are 39 students of the Japanese Language Education Program of UNESA which engaged in online learnings. The result of the research showed that there are some challenges faced by respondents, they are; a) online learning burdens them; b) internet connection is the biggest obstacle; and, c) they have not yet mastered information technology (IT). Nevertheless, the respondents hope that a) the learning keeps on going; b). There will be an internet quota as assistance; and, c) the pandemic stops soon. Meanwhile, the solutions they hope for are; a) internet quota assistance; b) empowerment of the educators and also the students.